Muntok Society in the Globalization Stream Political Ethnic Tionghoa and Malay - ., Yuliarni; ., Warto; Purwanta, Hieronymus (KnE Social Sciences, 2024)
With the passage of time and the tide of globalization, the city of Muntok has witnessed significant development. However, studies of Muntok relating to political changes in the last 10 years are still uncommon. This study focuses on the impact of political globalization on the interaction of Chinese and Malay ethnic communities in Muntok, Bangka. This study used qualitative approach with a literature or library study methodologies. According to the findings of the study, political globalization has the following effects: 1) increasing the use of public rights votes in general elections; 2) increasing the public vote of ethnic Chinese and Malay in political elections; and 3) increasing the involvement of Malaysians and Chinese in public elections because globalization does not arrange the vote for Chinese people. Many Malay people also choose the Tionghoa people. Finally, 4) there was a balance in the regional government in Muntok Bangka West between 2016 and 2019 (H. Parhan Ali (Malay ethnic) as Bupati and Markus (Tionghoa) as Deputy Bupati) and 2021–2026 (H. Sukirman as Bupati and Bong Ming Ming (Tionghoa) as Deputy Bupati). In conclusion, the significance of political globalization for the Muntok Bangka society is favorably evaluated, and the consequences of ethnic misunderstanding because of the Muntok society’s political globalization can be developed in historical learning material. Keywords: Muntok, politics, globalization, Tionghoa Malay, Bangka